“Naugolnye palaty” — 1st Cadet Corps in the First Half of the 18th Century: Presentation of the Archaeological Collection - Shmelev, Kirill V.; Muratbakieva, Anastasia D. (Actual Problems of Theory and History of Art, 2022)
This article deals with the archaeological and architectural research of the “Naugolnye palaty” building, a part of the Menshikov Palace, one of the early Petersburg buildings and the residence of the 1st Cadet Corps, and presents the early part of the archaeological collection. During the work, a sample of wooden architecture was found — an ice-chamber, and several other categories of archaeological finds. Among the individual finds are documents and paper products, fragments of weapons, uniforms, military equipment, civil clothes, shoes, children’s toys, dishes, decorations, details of furniture and interior. The finds have been made of paper, metal, leather, wood, glass, bone, and combinations of different materials. Those made of organic materials are unique. This article examines some of the finds relating to the beginning of the use of the complex in the first half — middle of the 18th century.
Keywords: early Petersburg; Menshikov Palace; Naugolnye palaty; 1st Cadet Corps; archaeological finds; ice-chamber; uniform; equipment; documents